Characteristic and Prognostic Value of Serum Bone Turnover Markers in Pregnant Women With Pre-Eclampsia: A Prospective Cohort Study - Fan Yu; Xiaocui Huang; Yuanting Tang; Yiduo Zhang; Qing Li; Yongmei Jiang (International Journal of Clinical Practice)
Conclusion: Pre-eclampsia patients may have an activated bone metabolism status compared with healthy controls. Pre-eclampsia patients with elevated bone resorptive marker ß-CTX should pay more attention to the risk of disease aggravation and adverse pregnancy outcomes.